Optimization design of an acoustic cover layer for a cylindrical cavity based on porous materials - Bohan ZHANG; Jili RONG; Xiuyan CHENG (工程科学学报)
During the launch and flight of carrier rockets, the acoustic and vibrational excitations generated by the external environment pose significant threats to their internal payloads. These disturbances, if not mitigated, can lead to structural fatigue or damage to sensitive equipment. To address this problem, porous materials, renowned for their lightweight and sound-absorbing properties, have been widely investigated and applied to noise reduction and vibration damping for payload fairings. In this study, a comprehensive investigation into the parameter fitting and acoustic performance optimization of porous materials is conducted, utilizing advanced physical models, multifluid impedance transfer theory, and particle swarm optimization algorithms. This research combines experimental approaches, including impedance tube experiments, with numerical methods, such as acoustic finite element analysis, to enhance the noise control capabilities of porous materials. This study employs three distinct porous materials, namely, melamine, polyester, and fiberglass, which are integrated into a multilayer porous acoustic coating. The design of this coating is based on the optimization of key parameters, including the thickness distribution and the arrangement of different layers. Various configurations were explored, and control groups were established to assess the improvements brought by the optimization process. Impedance tube experiments were conducted to measure the sound absorption coefficients of the multilayer porous acoustic coatings before and after optimization. Results showed a significant enhancement in the absorption performance, with a marked increase in the absorption coefficient across a broad frequency range. The underlying sound absorption mechanisms of the porous materials were analyzed to explain these improvements. To further validate the performance of the optimized multilayer porous acoustic coating, a cylindrical cavity experiment was conducted. This experimental setup simulated the cylindrical section of a carrier rocket payload fairing, providing a controlled environment to evaluate the noise reduction and vibration-damping effects of the coating. The findings showed that, after applying the optimized coating, the overall sound pressure level at various measurement points within the cavity decreased by at least 7.4 dB. The power spectral density of acceleration measured on the cylindrical wall was also significantly suppressed, particularly in the mid-to-high frequency ranges. Vibration suppression is critical for protecting the structural integrity of the payload fairing and the equipment housed within it. In addition to the experiments, acoustic finite element simulations were conducted to analyze the effects of the placement and coverage rate of porous materials on the noise reduction and vibration-damping performance within the cylindrical cavity. The simulation results showed that placing the porous materials closer to the sound source yielded better noise reduction results. However, increasing the coverage rate of the porous material did not lead to proportional improvements in noise reduction or vibration damping. This finding indicates that the design of the acoustic coating must carefully maintain a balance between noise protection and weight and space efficiency. In conclusion, this research highlights the significant potential of porous materials in enhancing noise and vibration protection for carrier rocket payload fairings. The optimized multilayer porous acoustic coating not only improves sound absorption but also delivers effective noise reduction and vibration suppression, providing valuable insights for aerospace applications. The findings indicate that the optimal placement and coverage design of porous materials are essential for achieving the desired protective effects while minimizing material usage and overall mass. These results contribute to the ongoing development of more efficient and lightweight noise control solutions for carrier rockets.